1971
DOI: 10.1073/pnas.68.8.1796
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Siomycin and Thiostrepton of Both Aminoacyl-tRNA and Factor G Binding to Ribosomes

Abstract: Siomycin, a peptide antibiotic that interacts with the 50S ribosomal subunit and inhibits binding of factor G, is shown also to inhibit binding of aminoacyltRNA; however, it does not impair binding of fMet-tRNA and completion of the initiation complex. Moreover, unlike other inhibitors of aminoacyl-tRNA binding (tetracycline, sparsomycin, and streptogramin A), siomycin completely abolishes the GTPase activity associated with the binding of aminoacyl-tRNA catalyzed by factor Tu. A single-site interaction of sio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(12 citation statements)
references
References 30 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…231233 These thiopeptides bind near the GTPase-associated center that engages a number of translation factors during initiation and elongation. 234236 Structural studies revealed that thiopeptides bind to a cleft between the ribosomal protein L11 and the 23S rRNA, and the precise intermolecular interactions differ according to the exact structural features of the thiopeptide. 231,237 Complexation of the ribosome and a thiopeptide disrupts the conformational changes ordinarily communicated from the translation factors to the ribosome, ultimately halting translocation along the mRNA template.…”
Section: Thiopeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…231233 These thiopeptides bind near the GTPase-associated center that engages a number of translation factors during initiation and elongation. 234236 Structural studies revealed that thiopeptides bind to a cleft between the ribosomal protein L11 and the 23S rRNA, and the precise intermolecular interactions differ according to the exact structural features of the thiopeptide. 231,237 Complexation of the ribosome and a thiopeptide disrupts the conformational changes ordinarily communicated from the translation factors to the ribosome, ultimately halting translocation along the mRNA template.…”
Section: Thiopeptidesmentioning
confidence: 99%
“…231,237 Complexation of the ribosome and a thiopeptide disrupts the conformational changes ordinarily communicated from the translation factors to the ribosome, ultimately halting translocation along the mRNA template. 229,233,235,236 A subset of thiopeptides, including the thiomuracins and GE2270A, exert a separate mode of antibacterial action by the inhibition of elongation factor Tu (EF-Tu). EF-Tu ordinarily delivers aminoacylated tRNAs to the ribosome following translocation.…”
Section: Thiopeptidesmentioning
confidence: 99%
“…The cyclic peptide thiostrepton is an efficient inhibitor of both translational GTPases, targeting initiation factor IF2 and elongation factors EF-Tu and EF-G on the ribosome (2628), and E. coli RelA (at least in the test tube [29, 30]).…”
Section: Introductionmentioning
confidence: 99%
“…This region is part of the GTPase-associated center (GAC), so named because it is involved in binding of translation factors and stimulation of their GTPase activities: Consistently, thiopeptide antibiotics have been shown to inhibit IF2-dependent 70S initiation complex (70SIC) formation (Brandi et al, 2004; Grigoriadou et al, 2007), EF-Tu-dependent delivery of aminoacyl-tRNAs to the ribosome (Brandi et al, 2004; Gonzalez et al, 2007; Modelell et al, 1971; Otaka and Kaji, 1974), translocation of the tRNA 2 -mRNA complex through the ribosome (Munro et al, 2010; Pan et al, 2007; Pestka, 1970; Pestka and Brot, 1971; Rodnina et al, 1997), and stringent factor RelA-dependent synthesis of ppGpp (Cundliffe and Thompson, 1981; Jenvert and Schiavone, 2005). Surprisingly, however, ThS and MiC exhibit differential effects on the uncoupled ribosome-dependent EF-G GTPase activities: ThS strongly inhibits multiple-turnover GTP hydrolysis of EF-G (Pestka, 1970; Weisblum and Demohn, 1970) by preventing Pi release and thus trapping EF-G on the ribosome (Rodnina et al, 1999; Seo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%